2017
DOI: 10.1039/c7ra11236j
|View full text |Cite
|
Sign up to set email alerts
|

Study on the cleavage of alkyl-O-aryl bonds by in situ generated hydroxyl radicals on an ORR cathode

Abstract: ˙OH selectively attacks the active sites opposite to phenolic hydroxyl groups and leads to bond-cleavage of ether bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…Volmer et al (Table , entry 7) studied the lignin ECOD with reticulated vitreous carbon foam electrodes and using two different ILs, 1-ethyl-3-methyl­imidazolium trifluoro­methanesulfonate ([emim]­[OTf]) and triethyl­ammonium methanesulfonate (TMS). They demonstrated the participation of electrogenerated H 2 O 2 or hydroxyl radicals (from the oxidation of intentionally added H 2 O) as both auxiliary oxidant and radical scavenger (as also observed in other works ), which inhibits the repolymerization of monomers under oxidative pathways. TMS and [emim]­[OTf] showed maximum lignin decomposition rates of 22–31 and 19–23 wt%, respectively.…”
Section: Demonstrated Electrochemical Routes For Conversion Of Interm...supporting
confidence: 70%
See 1 more Smart Citation
“…Volmer et al (Table , entry 7) studied the lignin ECOD with reticulated vitreous carbon foam electrodes and using two different ILs, 1-ethyl-3-methyl­imidazolium trifluoro­methanesulfonate ([emim]­[OTf]) and triethyl­ammonium methanesulfonate (TMS). They demonstrated the participation of electrogenerated H 2 O 2 or hydroxyl radicals (from the oxidation of intentionally added H 2 O) as both auxiliary oxidant and radical scavenger (as also observed in other works ), which inhibits the repolymerization of monomers under oxidative pathways. TMS and [emim]­[OTf] showed maximum lignin decomposition rates of 22–31 and 19–23 wt%, respectively.…”
Section: Demonstrated Electrochemical Routes For Conversion Of Interm...supporting
confidence: 70%
“…Several authors also studied the ECOD of lignin model molecules, ,, which can represent some specific linkages present in real lignin but do not show some of the most technologically challenging limitations of this macro-molecule such as low solubility in pH below 9, low diffusion coefficients (which limit the direct electrolysis) and the general recalcitrance.…”
Section: Demonstrated Electrochemical Routes For Conversion Of Interm...mentioning
confidence: 99%
“…Based on several well-designed experiments, it was confirmed that the main ROS was *OH. The degradation rate and product yield displayed a good positive linear relationship with the concentration of the electro-generated *OH on the ORR cathode [67]. This result indirectly proves that, compared with a single electrode, the synergistic effect of anode and cathode greatly increase the degradation efficiency of lignin.…”
Section: Degradation Of Lignin and Lignin Model Compounds By Ros Genementioning
confidence: 58%
“…The above phenomena indicate that the DR of PBP strongly depends on the amount of hydroxyl radicals (•OH) that are produced through catalyzed decomposition of H2O2. The decomposition of H2O2 follows the first-order kinetic reaction with reaction rate constants of 0.0121 min -1 at 20 °C, 0.0396 min -1 at 40 °C, and 0.0965 min -1 at 60 °C, respectively (Lei et al 2017). The amount of •OH increased when the initial concentration of H2O2, the dosage of catalyst, and the reaction temperature were increased.…”
Section: Optimization Of Degradation Conditionsmentioning
confidence: 99%
“…Lignin or lignin model compounds could be depolymerized by H2O2 oxidative degradation, in which the generated reactive oxygen species (ROS) act as oxidizing reagent (Kang et al 2019). Certain products are generated by selective cleavage of linkage bonds (Lei et al 2017;Jiang et al 2019). However, the product selectivity is reduced if a liquor having strong acidity (such as H2SO4) is used as the co-catalyst because over-oxidation of the products can occur, making product separation difficult.…”
Section: Introductionmentioning
confidence: 99%